3D modelling of electric field in vicinity of 400 kV power line. Issue 4 (8th August 2018) - Iatcheva, Ilona; Dimitrova, Malina; Petkova, Nikolina
Abstract : Purpose: The purpose of this study is to model the electric field distribution in 3D in the vicinity of 400 kV power line to determine the field impact on the environment and on the human body depending on the person location and presence of other objects. Design/methodology/approach: The real 3D geometry of the three-phase line because of the line sag presence and existence of additional objects in its vicinity is considered. The time-harmonic electric field has been modeled, taking into account 1, 200 phase shifting between the three-phase, 50 Hz currents. The study has been carried out using the finite element method (FEM) and COMSOL Multiphysics 5.2 software package. Special attention was paid to the field at a height of 2 m from the ground, to estimate the field influence on the located human body in the studied area (in relation to the limits for permissible electric field values). Findings: 3D map of electric field in the line vicinity and the electric field strength distribution along the observation surface (2 m from the ground) are determined for several region configurations: without additional objects, human presence just under the line, human at a certain distance from the line and presence of human and a tree. The simulation model was validated on the basis of comparison with computed and experimental data presented in the literature. Originality/value: 3D FEM modeling makes it possible to consider the real environment configuration, presence of line sag and additional objects with different material properties and obtaining of field quantities at any point of observation.